Measuring the value added intellectual capital on financial performance: a case of malaysian green technology companies / Noor Sharida Badri Shah and Noor Azuddin Yakob - Badri Shah, Noor Sharida; Yakob, Noor Azuddin (Universiti Teknologi MARA, Kedah, 2022)
The purpose of this study is to examine the relationship between Intellectual Capital (IC) components and financial performance of Malaysian green technology companies. IC consists f three main components which are Human Capital (HC), Structural Capital (SC) and Capital Employed (CA). The data are gathered from the annual report of ten (10) selected Malaysian green technology companies (Ecofriendly companies) from 2014 until 2018 in various industries. Empirical findings reported that Value Added Structural Capital (STVA) is the most significant factor compared to Value Added Human Capital (VAHU), Value Added Capital Employed (VACA) and Value Added Intellectual Coefficient (VAIC). It shows that the companies depended highly on STVA (the companies used database, process, competitive intelligence and system which resulted from the product or system that is created by a firm) to increase their financial performance. This study proved that structural capital is an important element in intellectual capital for green technology companies since it will lead to an effective and efficient business operation (less cost of operations) to sustain competitive advantage of the company.